Costumbres y tradiciones sobre medicina ancestral en salud curativa en la comunidad de San Lucas - Merchán Sinchire, Beatriz Marina (2016)
Ecuador is characterized by a complex cultural diversity, recognized by the Constitution, approved in 2008, as a multinational and multi-ethnic State, which affects demand for complementarity between medical systems. In the course of its history, 2 predominant models of health found the officer, biomedical, 'Western' or allopathic character and the traditional ancestral or indigenous peoples, also called Indian or pre-Columbian and Afro-descendants, the contradiction between these two models of health care reveals the epistemological order between different medical systems and Biomedicine hegemonism expressed in a set of contradictions in the social order. The descriptive, whose objectives were to identify customs and traditions on ancient medicine in curative health in the community of “San Lucas” belonging to the saraguro culture population, participated as a focal group 173 people older than 60 years, as a technique and instrument of data collection was used the interview. The results are: the community prevail respiratory and digestive diseases, the custom is to consult the "healer" as a traditional doctor in the 98.26%; traditional ancestral practices relate to the aromatic water consumption, use of "lucky charms", participation in "ceremony" and "spiritual rites", protection of "hot" and "cold" elements, and use of medicinal plants for home protection against "evil" or "I bemusement". KEY WORDS: custom; traditions; ancestral medicine.